Evaluation of the Impact of Existing Condition and Overlay Characteristics on Asphalt Overlay Design and Performance based on a Mechanistic-Empirical Approach - F. Jasim, Abbas; F. Al-Saadi, Israa; F. Al-Saadi, Anmar (International Journal of Engineering and Technology, 2018)
The present study sought to determine how the overlay design and performance of asphalt concrete (AC) were affected by existing pavement condition and overlay material properties. To that end, this study was performed in different scenarios of traffic and structure with the latest AASHTO design software AASHTOWare (version 2.3). The modulus and rut depth of existing layers, the interface condition between AC overlay and existing pavement, and the AC overlay properties of Poissonâ€™s ratio and performance grade were addressed in the current study. Besides the overlay thickness design, the investigation also focused on pavement performance to determine how separate distresses were impacted by existing pavement condition and the properties of the overlay material. The investigation produced three major outcomes, as follows: the current AC layer thickness and design traffic determined the extent to which the existing AC layer condition affected the overlay design thickness; the overlay performance and design were not significantly affected by the existing base and subgrade condition; and fatigue cracking was more strongly influenced by the existing AC layer modulus and interface bonding condition compared with the rutting potential.Â